Gender non-fiction — uwagi wstępne - Śmieja, Wojciech; Lisowska, Katarzyna (Zagadnienia Rodzajów Literackich, 2024)
The introduction to the thematic issue of “The Problems of Literary Genres. Forms of Culture and Theory,” focuses on gender-oriented interpretation of non-fiction literature (reportage, biography, autobiography, essay, etc.) and consists of two parts. In the first, we present the theoretical background for undertaking a gender-sensitive reading of non-fiction literature, highlighting that the nature and status of the research questions is somewhat different from that of literature identified as fiction, due to the characteristics of the factuality/fictionality relationship in non-fiction genres, as well as the specific evolution of this literary subfield. In the second section, we analyse various — often fragmentary — examples of readings and interpretations in which the gender status of the author/character and even the genre itself was questioned and debated. We note that these readings and the disputes that have also occurred do not accumulate into any compact interpretation. We briefly discuss the themes of the essays presented in this issue and emphasise the need for more research and gender-oriented readings of non-fiction literature.